A report card assessment of the prevalence of healthy eating among preschool-aged children: a cross-cultural study across Australia, Hong Kong, Singapore, and the US - Wan, Alison Wing Lam; Chung, Kevin Kien Hoa; Li, Jian-Bin; Xu, Shebe Siwei; Chan, Derwin King Chung (Frontiers in Nutrition, 2024)
Objective: This study aimed to initially adopt an International Healthy Eating Report Card for Preschool-aged Children to assess the prevalence of healthy eating behaviours and favourable family home food environments (FHFEs) among preschool-aged children in Australia, Hong Kong, Singapore, and the US. We also examined which cultural contexts would exhibit significant differences in the report card scores among the four cultural contexts.: In this cross-cultural study, 2059 parent-child dyads, with approximately 500 dyads in each cultural context, were recruited. The parents were asked to complete the validated International Healthy Eating Report Card Scale to assess the dimensions of the Report Card (i.e., Indicator of Children's Eating Behaviours: (1) Children's Dietary Patterns and (2) Children's Mealtime Behaviours, and Indicator of FHFEs: (3) Parental Food Choices and Preparation, (4) Home Healthier Food Availability and Accessibility and (5) Family Mealtime Environments). Each indicator received a letter grade (i.e., A (≥ 80%) = excellent, B (60-79%) = good, C (40%-59%) = fair, D (20%-39%) =poor, F (<20%) = very poor and including the plus (+) and minus (-) signs) to represent the proportion of participants who could meet the predefined benchmarks. We also employed ANCOVA and Bonferroni's post-hoc test to examine the differences in the report card scores between the four cultural contexts. A significance level was set at p < .05.The average overall report card grade across the four cultural contexts was "B-" (Good), ranging from "C+" (Singapore and the US) to "B-" (Australia and Hong Kong). The average grade for Children's Eating Behaviours was classified as Fair ("C-"), while the average grade for FHFEs was classified as Good ("B+") for all cultural contexts. A comparison of the overall report card scores revealed that Australia exhibited a significantly higher report card score than Singapore and the US, while Hong Kong achieved a significantly higher score than Singapore.The International Healthy Eating Report Card provided an overview of the prevalence of healthy eating in different cultural contexts. We believe that the International Healthy Eating Report Card may offer new perspectives on interventions for fostering healthy eating in young children.